Advanced Content Analysis : Can Artificial Intelligence Accelerate Theory-Driven Complex Program Evaluation? - Franzen, Samuel; Quang, Cuong; Schweizer, Lukas; Budzier, Alexander; Hrstich, Peter; Reissfelder, Stéphane; Gold, Jenny; Vellez, Mercedes; Ramirez, Santiago; Raimondo, Estelle (World Bank, Washington, DC, 2022)
This pilot study tests the applicability, usefulness, and added value of using AI for advanced theory-based content analysis within the framework of IEG’s thematic evaluations. Using a set of interventions associated with the World Bank’s chronic malnutrition and stunted growth portfolio, the paper assesses the efficiency gains generated by AI-assisted content analysis in labeling and classifying text according to an outcome-based conceptual framework.